The dynamics of self-employment in East Germany: an empirical analysis using panel data and allowing for state dependence and endogenous attrition - Michael Lechner (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1993)
The focus of the paper is on the analysis of the individual determinants of self-employment in East Germany after unification, with special respect to the dynamic issues which may arise. The data set used is the Arbeitsmarkt-Monitor für die neuen Bundesländer, which is a panel data set consisting of four waves covering the period from November 1990 to November 1991. The attrition rate in this data set is high. The data set and the economic questions of interest give raise to methodological issues concerning estimation techniques for limited dependent variable models on panel data. Smooth Simulated Maximum Likelihood methods are proposed to allow for state dependence as well as endogenous attrition in the estimation. The results indicate the importance of the dynamics which drive the emergence of the small business sector in East Germany. Other important factors appear to be human capital aspects, institutional restrictions, expectations about the future of the local economy, the profession in 1989 and martial status. The simulations performed confirm the importance of the dynamics and suggest that self-employment in East Germany might reach the level of self-employment in West Germany as soon as 1995.
Keywords: 330; Selbstständige; Mikroökonometrie; Simulation; Neue Bundesländer